Minimum dwelling - Broto, Eduard (Barcelona : Links, 2010)
Contributions from award-winning architects from around the globe along with young emerging talent are brought together in this book to provide a source of inspiration for anyone who dares to experiment with space. All the projects are illustrated with full-color photographs and accompanied by explanatory texts offering the reader the opportunity of venturing into the innovative world of Minimum Dwellings.
boek